Electronic Government Procurement (e-GP): A solution to institutional challenges in Zambia’s Medical Supply Chain or another technical solution? - Chenga, Kaputo Melody (Graduate School of Development Policy and Practice, 2020)
Do technical solutions override or fast track institutional reforms? This study interrogates the extent to which Zambia’s newly introduced Electronic Government Procurement (e-GP) is addressing the procurement challenges [for essential drugs and medical supplies] in the Ministry of Health (MoH). A brain child of the Zambia Public Procurement Authority (ZPPA), the e-GP is but one of the components of the wider procurement reform agenda. The e-GP was introduced with the intention of enhancing efficiency, effectiveness and Value for Money (VfM) in public procurement. Since 2016, ZPPA has been piloting the approach in selected Procurement Entities (PEs), a combination of sector ministries and state parastatals. Based on review of project documentation, publicly available data, and interviews from key stakeholders; the study explores and interrogates the contextual and institutional challenges characterising the e-GP design and pilot implementation phases, and the extent to which these realities impact the achievement of the intended outcomes. A fair amount of information from interviewees was provided under conditions of confidentiality, thus individuals are not often identified. It is perhaps too early to ascertain the extent to which the e-GP is realising the intended objectives. This is partly explained by the project’s slow start, occasioned by delayed procurement which had knock - on effects on the overall project’s pace. An interrogation of the history and political economy of Zambia suggests however that it is the opaque challenges bordering on the political economy which is the single most binding constraint to reforms; defining the process, the pace and outcomes. The design of the e-GP was generic and non-participatory. There is no evidence to suggest that the process had provided opportunity for PE’s to define and customize the problems that mattered for them to be addressed by the e-GP. Instead, the e-GP seems to have been sold to PEs as a best practice solution. Because of the deep incentive fabric at both organizational and individual levels, the project seems to have some traction. Effort of various actors does not appear to be supportive of each, often latently contradicting each other. Project progress is held constant by the relative ability of the ZPPA to push some strands of work within some pilot PEs. This relative ability of the ZPPA shields the low levels of acceptance and questionable authority within PEs and among actors. Progress on the e-GP appears like a façade of success; suggestive of isomorphic mimicry.